> > f(x)= x + 5 g(x)= x^2 - 4x + 5 h(x)= 3x^2 -2x + 5 first solve h[ f (5) ] - g [ h (1) ] then ( f+ g ) ( x )

f(x)= x + 5 g(x)= x^2 - 4x + 5 h(x)= 3x^2 -2x + 5 first solve h[ f (5) ] - g [ h (1) ] then ( f+ g ) ( x )

f(x)= x + 5 g(x)= x^2 - 4x + 5 h(x)= 3x^2 -2x + 5 first solve h[ f ...

303 Views

f(x)= x + 5 g(x)= x^2 - 4x + 5 h(x)= 3x^2 -2x + 5 first solve h[ f (5) ] - g [ h (1) ] then ( f+ g ) ( x )

f(x)= x + 5 g(x)= x^2 - 4x + 5 h(x)= 3x^2 -2x + 5 first solve h[ f (5) ] - g [ h (1) ] then ( f+ g ) ( x )

Answer

f x =x+5 g x =x 2-4x+5 h x =3x 2-2x+5 h f 5 -g h 1 = ----------------- f 5 =5+5=10 h f 5 =3 10 2-... f+g x = x+5 + x 2-4x+5 =x 2-3x+10

To see more answers head over to College Study Guides
Virtual Teaching Assistant: John B.
Question Level: Basic
Karma: Free
Upload Date: 5/31/2017

This 70 words question was answered by John B. on StudySoup on 5/31/2017. The question contains content related to Math Since its upload, it has received 303 views.

Recommended Questions